"Audientia sacerdotalis"? - Remarks on the Legal Nature of Dispute Resolution by Ecclesiastics in Late Antiquity - Wojtczak, Marzena ca. 20./21. Jh. (2021)
The problem of audientia episcopalis in late antiquity has been the subject of extensive research in the past. Previous studies have usually focussed on the legal doctrine, as well as the picture of bishop courts in the light of the literary sources. In contrast, the question of how audientia episcopalis functioned in the legal practice as shown by papyri has caused scholars much difficulty, due to the limited material available as well as the obscure nature of the institution. One could therefore ask: how is it possible that such allegedly common practice of dispute resolution by the bishops - as literary sources make us believe - is so elusive in the papyri? How to explain the simultaneous increase for that period of the papyrological attestations regarding arbitration/mediation carried out by the clergy of lower rank? Could we be dealing with some sort of audientia sacerdotalis functioning in the legal practice? How widespread was in fact the audientia episcopalis, and was this institution homogeneous or rather heterogeneous in nature? The paper presents the attempt to answer these questions by confronting the imperial law with the evidence of legal practice.
Keywords: Justinian; Roman Law; alternative dispute resolution; Arbitration; audientia episcopalis; Bishops; Clergy; Late Antiquity; legal practice; Mediation; Monks; Papyrology; presbyters